Community-based participatory research: foundations, requirements and challenges for researcher - João Lucas Campos de Oliveira; Ana Maria Müller de Magalhães; Juliana Aparecida Peixoto Nishiyama; Dagmar Willamowius Vituri; Sonia Silva Marcon; Laura Misue Matsuda (Universidade Federal de Santa Maria, 2019)
Objective: To describe theoretic and philosophic foundations and possible applications of Community-Based Participatory Research. Method: theoretical reflection focused on this approach's transformative potential in Public Health scope. Results: in this research modality, community partners are valued at all stages of the investigative process, helping to design interventions that meet their needs. In addition, spaces and production instruments are created, and ideas, practices and care alternatives are disseminated, in order to facilitate the transposition of language and communication barriers between service professionals, researchers and health system users. In the Community-Based Participatory Research context, daily care management is based on cultural dialogue and sharing of chores, which develops mutual trust and sustainability of the researcher-community interaction process. Final Considerations: Community-Based Participatory Research is an important methodological approach to understand the human complexity and advances in community nursing.